2021
DOI: 10.1039/d1bm00210d
|View full text |Cite
|
Sign up to set email alerts
|

A 3D pancreatic tumor model to study T cell infiltration

Abstract: Human T cell infiltration across the endothelium in a 3-dimensional pancreatic tumor model in relation to activation and cellular components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…49 As demonstrated, 50–55 the stroma represents a histopathological hallmark of pancreatic ductal adenocarcinoma and plays a fundamental role in tumor progression. 56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro , 17,20,28,33,34,58–61 the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. 62–64…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…49 As demonstrated, 50–55 the stroma represents a histopathological hallmark of pancreatic ductal adenocarcinoma and plays a fundamental role in tumor progression. 56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro , 17,20,28,33,34,58–61 the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. 62–64…”
Section: Discussionmentioning
confidence: 99%
“…49 As demonstrated, [50][51][52][53][54][55] the stroma represents a histopathological hallmark of pancreatic ductal adenocarcinoma and plays a fundamental role in tumor progression. 56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro, 17,20,28,33,34,[58][59][60][61] the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. [62][63][64] We report herein the design, development and characterization of a multilayer PDAC-on-chip device to mimic the tumorstroma relationship through the culture of human pancreatic ductal epithelial cells expressing the activated KRAS and human pancreatic stellate cells, on the same miniaturized platform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cells interact with endothelial cells, during angiogenesis, primarily to ensure oxygen and nutrient supply to the tumor. However, tumor endothelial cells also shape the overall PDAC tumor microenvironment, notably by acting as a selective barrier that governs immune cells' access to the tumor site [34]. Tumor endothelial cells can therefore regulate the amplitude and the efficacy of anti-tumor responses [7].…”
Section: Tumor Endothelial Cellsmentioning
confidence: 99%